Correction to: Real-World Recurrence Rates and Economic Burden in Patients with Resected Early-Stage Melanoma - Sekwon Jang; Tayla Poretta; Tarun Bhagnani; Qing Harshaw; Matthew Burke; Sumati Rao (Adis, Springer Healthcare, 2020)
The presentation of the numbers of patients in Tables 1 and 3 was adjusted